Analysis of external resources in agricultural production - Jiménez-Velázquez, Mercedes A.; González- Burgos, Gerardo (Revista Mexicana de Ciencias Agrícolas, 2017)
This paper is oriented to analyze the investment of external  resources (remittances) for agricultural production; through  programs aimed at promoting rural development. The aim of  the study is to identify transformations, aimed at proposing  productive projects with technological innovations  in producers who adopt them in terms of knowledge,  social, organizational and economic relations to improve  their social welfare. The research was carried out with  agricultural producers in the community of San Pablo Güila,  Municipality of Santiago Matatlán, Oaxaca. Methodology  was used with a mixed approach: quantitative, applying a  questionnaire to heads of families of Zapotec origin; and  qualitative studies using social research techniques: direct  and participatory observation. Results evidenced changes in  production, family and group organization, reflecting that  the external support received by migrant relatives living in  the United States of America, its destination is linked to the  investment on the productive project and affects the way  of thinking of the producer, Promotes training and food  that tends to a socioeconomic, educational, productive and  technological improvement. The importance of the role of  remittances in improving the standard of living is perceived.
Keywords: productive project, remittances, San Pablo Güila, Oaxaca, socio-economic transformation